Lexicalization Indicators of Thai Words - Maluleem, Lena (Journal of Letters, 2023)
The present study proposes quantitative measurements for the degree of lexicalization. The study suggests that degree of lexicalization can be measured using three quantitative indicators including reaction time, which represents the degree of morphosyntactic change, semantic compositionality, which represents the degree of semantic change, and usage frequency, representing the degree of change in usage. The results show that all three indicators can distinguish between non-lexicalized and highly lexicalized constructions. In addition, the findings indicate that each aspect of change in lexicalization occurs at a varying rate and time. Consequently, the degree of lexicalization of a construction cannot be represented by a single indicator but must be determined using a combination of indicators.